how to pair android with airpods - rosari J (EDUCAFL : Journal of Education of English as Foreign Language, 2018)
You're mistaken if you believe AirPods are solely compatible with Apple products. As long as you have a Bluetooth connection, you can use AirPods and AirPods Pro on Android.The Bluetooth standard is used by millions of devices including Android. Bluetooth and many of the codecs in AirPods are compatible with Android and PC, not only Apple. Samsung, LG, Nokia, and Google Pixel users may find AirPods to be a viable alternative.